Implementation of international experience in reforming the institute of public administration - Zagurskyy O.; Hubska O.; Slobodian I. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. Formulate the author’s own approaches to to the implementation of the international experience of reforming the public administration institute in the context of the modernization of public administration bodies in Ukraine. Methodology. The methodology includes a comprehensive analysis and a synthesis of available scientific and theoretical information. It is includes the formulation of relevant conclusions and recommendations. Such methods of scientific knowledge were used: terminological, logical-semantic, functional, systemic-structural, logical-normative. Results. The study recognized that the comparative analysis of the institute of public administration shows that European countries have different historical and institutional foundations, which is reflected in the form and content of their administrative reforms. In many ways, the administrative systems of individual European countries are very different from the models in the Anglo-Saxon countries, which, in turn, affects the path of European countries to public administration reform. At the same time, the reforms of the public administration system in European countries that adhere to the Napoleonic administrative model deviate significantly from the Anglo-Saxon model of administrative reforms. From this point of view, the thesis of general convergence towards a new model of public management can hardly be substantiated. Ukraine needs such a system of public administration, which is able to analyze and identify problems arising in society at an early stage, propose measures to solve them and successfully implement them. Originality. The study found that the transformation of public administration is inevitable, since modern national forms of government and management are incompatible with the needs of the new socio-economic practice of a globalizing society. At the same time, without transformation, it is impossible to achieve a qualitatively new level of management, the main characteristics of which can be synthesized. Reforms in European countries should not be considered only in the context of new public management, and therefore associated only with this concept. Alternative models of reforms in the countries of continental Europe are generally characterized as variants of the neo-Weberian type of reforms. Practical significance. The results of the study can be used during the development of provisions, conclusions and recommendations regarding the state strategy for the development of public administration, to increase the level of appropriate state decision-making in this area, as well as for further improvement of legislation in public administration.